A lattice boltzmann simulation for modeling the non-newtonian blood flow - Sriyab,S. (Research India Publications, 2015)
© Research India Publications. The Lattice Boltzmann method (LBM) is used to simulate the flow of non- Newtonian blood, considering that viscosity is a function of the velocity gradient in the Casson model. Analytical solutions have been derived to validate the Lattice Boltzmann scheme. The agreement between the velocity profile of LBM for non-Newtonian blood and the profile values obtained in the analytic solutions is excellent. Therefore, LBM can be used as a tool to study the blood rheology in the non-Newtonian model. The numerical results of LBM are found to be corresponding to the experimental result that blood behaves in a non-Newtonian manner at low shear rates and becomes Newtonian at high shear rates.